Emotions and Literary Engagement in the Representation of Social Reality / Emocije i književni angažman u prikazivanju društvene stvarnosti: The Function of Fear in Damir Pilić's Novel "As if everything is Normal" / Svrha straha u romanu Damira Pilića "Kao da je sve normalno" (Pregled: časopis za društvena pitanja / Periodical for social issues, 2025)
Considering the importance of the cultural coding of emotions and the number of current studies that investigate the expression, representations and functions of emotions in literary texts, and starting from J.P. Sartre’s theses on human emotions and engagement presented in his essay Engaged Literature, this paper will connect these two phenomena by investigating representation and the function of fear in the novel by the contemporary Croatian writer, Damir Pilić, Kao da sve je normalno (As If Everything’s Normal) (2018). Sartre defines emotion by anticipating contemporary constructivist and cultural approaches when claiming that emotion is always an expression of a certain way of life and worldview common to a class or an entire age. Thematizing the post-war reality in Bosnia and Herzegovina and Croatia and dealing with the consequences of the traumas left on citizens by war crimes, Pilić represents fear as the central emotion of his novel on the levels of its content, symbolism and genre. After explaining the relationship between emotions and literary engagement in the representation of social reality (according to J.P. Sartre), the analysis of the text in question will develop the hypothesis that Pilić posits fear as Sartre's "synthetic unity of affectivity", meaning that every feeling and every form of psychic life is actually a manifestation of the individual's social position and is closely related to the feeling of the collective. This paper will also consider how the author's intentions affect form and creative process (the genre hybridization of the political and social novel with elements of narrativized photo reportage and horror).
Keywords: emotions; emotionology in literature; literary engagement; representation of social reality; fear; post-war trauma; genre-hybridization of novel; J. P. Sartre; D. Pilić